STUDI KELAYAKAN BISNIS DARI ASPEK TEKNIS DAN OPERASIONAL - Ananda Putri Savana; Devri Azwan; Lina Anggara (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to look at the importance of technical and operational aspects for starting a business. Research uses literature or literature studies where researchers rely on reviewing written sources such as scientific journals, reference books, encyclopedias, and other reliable sources either in written form or in digital format that are relevant and related to the object being researched. The results and discussion obtained on the importance of technical aspects and operational aspects in business feasibility studies, entrepreneurs can make smarter decisions and minimize financial risks.